Модифицированный метод проектирования одного класса нечетких цифровых регуляторов - Гостев, В.И. (Проблемы управления и информатики, 2009)
На розвиток методу проектування одного класу нечітких регуляторів, що базується на аналітичних виразах для керуючих впливів на виході нечіткого регулятора за різних функцій приналежності, представлено модифікований метод, який дозволяє значно спростити проектування одного з трьох основних блоків нечіткого регулятора. In development of the method of designing of one class of the fuzzy controllers based on received analytical expressions for controlling actions on an output of the fuzzy controller at various membership functions, the modified method allowing to simplify considerably designing of one of three main units of the fuzzy controller is submitted.